G626 Use of long acting guanfacine in adhd and assessing the comorbidity and parents' perceptions. (25th October 2020) - Yemula, C; Ajmal, S; Sesham, R; Banerjee, T
Abstract : Aims: A study was conducted to find out the clinical indications, prior stimulant use, associated comorbidity and parents/carers' perceptions on the use of long acting guanfacine in children and adolescents with ADHD. Methods: The number of patients with ADHD on guanfacine over a period of 9 months were identified through IT support and their clinical records were accessed from our electronic system. Parents/carers' comments were also noted in relation to their child's progress. Results: 22 patients (17 boys and 5 girls) aged 7–16 years were commenced on guanfacine, with 50% aged 13 years and above. All the patients had one or more associated comorbid conditions varying from sleep problems (50%), autism spectrum disorder (40.9%), anxiety (18%), oppositional defiant behaviour (18%), learning disability (9%) and sensory processing problems (4.5%). 21 patients previously received various formulations of either methylphenidate or amphetamine medications. However, one patient with a diagnosis of William's syndrome with cardiac problems was commenced on guanfacine as the 1st option, following recommendation from a cardiologist. In 19 patients (86.3%) the stimulant medication was not found to be effective, not tolerated in 2 patients (9%) and not suitable in 1 patient (4.5%). The stable/maintenance dose of guanfacine was noted to be 1 mg for 5 patients (22.7%), 2 mg for 9 patients (40.9%), 3 mg for 6 patients (27.2%) and 5 mg for 2 patients (9%). Towards clinical outcomes, 14 parents/carers (63.6%) provided comments such as the child/adolescent is less aggressive, good symptom control, sleeping better, good start to school, best medication so far, much calmer and 'it is absolutely amazing!' Conclusion: Our study revealed that long acting guanfacine can be useful when the stimulant medication is not effective, not tolerated or not suitable. This complies with the current NICE guidelines. Despite a significant comorbidity, a high level of parents/carers' satisfaction is noted in our group.